Lipidomic diversity and proxy implications of archaea from cold seep sediments of the South China Sea - Zhang, Tingting; He, Wei; Liang, Qianyong; Zheng, Fengfeng; Xiao, Xi; Zeng, Zhiyu; Zhou, Jingzhuo; Yao, Wenyong; Chen, Haodong; Zhu, Yuanqing; Zhao, Jing; Zheng, Yan; et al. (Frontiers in Microbiology, 2023)
Cold seeps on the continental margins are characterized by intense microbial activities that consume a large portion of methane by anaerobic methanotrophic archaea (ANME) through anaerobic oxidation of methane (AOM). Although ANMEs are known to contain unique ether lipids that may have an important function in marine carbon cycling, their full lipidomic profiles and functional distribution in particular cold-seep setting are still poorly characterized. Here, we combined the 16S rRNA gene sequencing and lipidomic approaches to analyze archaeal communities and their lipids in cold seep sediments with distinct methane supply from the South China Sea. The archaeal community was dominated by ANME-1 in the moderate seepage area with strong methane emission. Low seepage area presented higher archaeal diversity covering Lokiarchaeia, Bathyarchaeia, and Thermoplasmata. A total of 55 core lipids (CLs) and intact polar lipids (IPLs) of archaea were identified, which included glycerol dialkyl glycerol tetraethers (GDGTs), hydroxy-GDGTs (OH-GDGTs), archaeol (AR), hydroxyarchaeol (OH-AR), and dihydroxyarchaeol (2OH-AR). Diverse polar headgroups constituted the archaeal IPLs. High concentrations of dissolved inorganic carbon (DIC) with depleted δ 13 CDIC and high methane index (MI) values based on both CLs (MI CL ) and IPLs (MI IPL ) indicate that ANMEs were active in the moderate seepage area. The ANME-2 and ANME-3 clades were characterized by enhanced glycosidic and phosphoric diether lipids production, indicating their potential role in coupling carbon and phosphurus cycling in cold seep ecosystems. ANME-1, though representing a smaller proportion of total archaea than ANME-2 and ANME-3 in the low seepage area, showed a positive correlation with MIIPL, indicating a different mechanism contributing to the IPL-GDGT pool. This also suggests that MIIPL could be a sensitive index to trace AOM activities performed by ANME-1. Overall, our study expands the understanding of the archaeal lipid composition in the cold seep and improves the application of MI using intact polar lipids that potentially link to extent ANME activities.